Increasing Community Legal Awareness Through Registration of Land Ownership Rights for the Cangkol Village Community - Wardah Yuspin; Syaifuddin Zuhdi; Andria Luhur Prakoso; Fafta Aini Putriana; Amanda Putri Ariyani (Jurnal Pengabdian Masyarakat Bestari, 2023)
Land registration is an important thing that must be done so that legal certainty and legal guarantees can be realized immediately. In this case, the purpose of this dedication is so that the people of Cangkol Village can understand and understand how vital land registration is. The method used in this service is to conduct legal counseling for the people of Cangkol Village and follow up with legal consultations. The service results are increasing legal awareness among the people of Cangkol Village, most of whom have understood and understand the importance of registering their land to protect their rights. The success of this service is that almost all the land in Cengkol Village has been registered and certified.